Fixed points for four maps related to generalized weakly contractive condition in partial metric spaces - Mahmoud, Bousselsal; Jazmati, M.S. (International Journal of Applied Mathematical Research, 2015)
We prove a unique fixed point theorem for a function depending from four self maps satisfying (Ï†-Ïˆ)-contractive condition in partial metric spaces. Presented results extend and generalize some existing fixed point results in the literature
Keywords: Partial Metric; Weakly Compatible Maps; Complete Space.